Billing Systems and Customer Satisfaction in the Ministry of Water and Environment Uganda: A Case of Kabale South Western Umbrella of Water and Sanitation. - Ayebare, Ivan (Kabale University, 2024)
Despite efforts to improve operations and performance, South Western Umbrella of Water and Sanitation has not met the minimum performance standards for collection efficiency, response rate, and customer care. This study examines the factors contributing to these shortcomings and gathers customer feedback to find solutions for enhancing service quality. The study focused on "Billing systems and customer satisfaction in the ministry of water and environment, Uganda, Uganda, specifically within the Kabale South Western Umbrella of Water and Sanitation." Justification for the study is that it generated additional knowledge about MOWE billing system and customer satisfaction in the perspective of revenue collection efficiency, response rate and customer care. It aimed to achieve the following objectives: firstly, to assess the impact of postpaid MOWE billing system on collection efficiency; secondly, to examine the influence of pre-paid MOWE billing system on response rate; and finally, to establish the relationship between MOWE billing systems and customer care. The research employed a cross-sectional research design, incorporating both quantitative and qualitative methodologies. A sample size of 136 respondents was selected from a population of 210 determined using the statistical table of Krejcie & Morgan (1970), of which 132 actually participated in the study giving a response rate of 97.1%. Findings regarding the first objective revealed that the response rate in Kabale South Western Umbrella of Water and Sanitation is affected by the pre-paid MOWE billing system, suggesting a need for the ministry to enhance public awareness of its policies and procedures. Regarding the second objective, the analysis demonstrated a significant and positive correlation between the MOWE Billing System and response rate. Finally, the third objective aimed to establish the relationship between MOWE billing systems and customer care. Descriptive statistics indicated that 90% of respondents agreed on the existence of a relationship between MOWE billing systems and customer care, with a correlation coefficient of 0.829 in the record-keeping system on service delivery. In conclusion, the study found positive and significant correlations among all three objectives.